Geostatistical Modeling using Ordinary Kriging for Estimating Nickel Resources in Sulawesi Indonesia - Marwanza, Irfan; Putra, Danu; Azizi, Masagus Ahmad; Dahani, Wiwik; Gumay, Rhazes Eesha; Sahetapy, Silvia Immanuela (Pandawa Institute, 2025)
Geostatistic is a statistical tool used in the mining sector to estimate and classify mining resources at a specific location. The purpose of this study was to evaluate the distribution or model of nickel resources, as well as estimate and classify nickel resources using a geostatistical approach. This study used data from exploration drilling at one of the nickel mining concessions in Sulawesi, Indonesia. The data set included 464 drill holes with an average distance of 50–100 m. The initial stage in this study was to develop a geological model, followed by descriptive statistical analysis, with the results of the variance coefficient ranging from 0.5 to 1.5 and normal distribution, indicating that the ordinary kriging method can be used and is considered adequate to produce sound and consistent findings. The values obtained from the variogram analysis on the spherical model will be used as parameters in the ordinary and efficiency kriging processes. Based on the estimation and classification of nickel resources using ordinary and efficiency kriging, the total measured, indicated, and inferred nickel resources are 39, 1.25, and 3 million tons, respectively, with an average Ni content of 1.16%.